New Water and Air Pollution Sensors Added to the Sonic Kayak Citizen Science System for Low Cost Environmental Mapping. Issue 1 (12th August 2021) - Griffiths, Amber G. F.; Garrett, Joanne K.; Duffy, James P.; Matthews, Kaffe; Visi, Federico G.; Eatock, Claire; Robinson, Mike; Griffiths, David J.
Sonic Kayaks are low-cost open-source systems for gathering fine-scale environmental data. The system is designed to be simple to fit on to standard kayaks or canoes, and full instructions have been made available for anyone wishing to build their own. The previous version included temperature sensors and a hydrophone for recording underwater sound. Here we outline the design and integration of two new sensors, for underwater turbidity and above water air particulate pollution. All sensors record continually, and the GPS location, time and date are also stored for every data point, allowing fine-scale environmental data mapping. The data being collected by the sensors is sonified (turned into sound) in real-time, allowing the paddler to hear the data as they are collecting it, making it possible to locate and follow interesting occurrences. We present proof-of principle data for the first time for all the sensors, demonstrating how the system can be used for environmental mapping, and discuss potential future applications and adaptations. We believe the Sonic Kayak system offers particular promise for citizen science and environmental activism, and allows professional researchers to gather data that was previously difficult or impossible to obtain.